The Relationship between Hospital Selection by Employer and Disabilities in Occupational Accidents in Korea - Joonho Ahn; Min Jang; Hyoungseob Yoo; Hyoung-Ryoul Kim (Elsevier, 2022)
Background: In the event of an industrial accident, the appropriate choice of hospital is important for worker health and prognosis. This study investigates whether the choice of hospital by the employer in the case of industrial accidents affects the prognosis of injured employees. Methods: Data from the 2018 Panel Study of Workers' Compensation Insurance in Korea were used in an unmatched case-controlled study. The exposure variable is "hospital selection by an employer," and the outcome variable is 'worker's disability." Odds ratios (ORs) were estimated by modified Poisson regression and adjusted for age, gender, underlying disease, injury severity, and workplace size and stratified by industrial classification. The group at increased risk was analyzed and stratified by age, gender, and area. Results: In the construction industry, hospital selection by the employer was significantly associated with increased risk of disability (adjusted OR 1.26; 95% confidence interval [CI]: 1.20-1.32) and severe disability (adjusted OR 1.38; 95% CI: 1.08-1.76) among the injured. Female and younger workers not living in the Seoul capital area were more at risk of disability and severe disability than those living in the Seoul capital area. Conclusions: Hospital selection by employers affects the prognosis of workers injured in an industrial accident. For protecting workers' health and safety, workplace emergency medical systems should be improved, and the selection of appropriate hospitals to supply treatment should be reviewed.